BEL499: Communication and interpersonal skills / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
This course aims to provide students with the necessary skills to perform at employment interviews. Students are prepared to design resumes, write application letters and are guided to answer questions posed at employment interviews. The course also provides students with communication and interpersonal skills essential for their personal and professional growth.